Tax Dispute Analysis 0f Surface Water Tax (Review Decision Number 2791/B/PK/PJK/2019) - Intan Puspanita; Asih Machfuzhoh; Mulyanah Mulyanah (Journal of Applied Business, Taxation and Economics Research, 2021)
The surface water tax creates different perceptions due to differences in the imposition of taxes regulated in regional regulations and contracts of work, one of which contains tax provisions that apply specifically. This study discusses a review of the arguments for the Judicial Review Decision Number 2791/B/PK/PJK/2019). This study uses literature research methods. The results of this study concluded that the panel of judges granted the appeal applicant on the basis that the Papuan provincial government could not collect surface water tax because it was not in accordance with article 32A and article 33A of the income tax law and the contents of the contract of work.